Root-zone fertilization improves crop yields and minimizes nitrogen loss in summer maize in China. Issue 1 (December 2018) - Jiang, Chaoqiang; Lu, Dianjun; Zu, Chaolong; Zhou, Jianmin; Wang, Huoyan
Abstract It is urgently to minimize nitrogen (N) loss while simultaneously ensuring high yield for maize in China. A two-year field experiment was conducted to determine the effects of root-zone fertilization (RZF) and split-surface broadcasting (SSB) on grain yield, N use efficiency (NUE), and urea-15 N fate under different N rates (135, 180 and 225 kg ha−1 ). Results showed that RZF increased grain yield by 11.5%, and the N derived from fertilizer (Ndff%) by 13.1–19.6%, compared with SSB. The percentage of residual15 N in the 0–80 cm soil was 37.2–47.4% after harvest; most15 N (64.4–67.4%) was retained in the top 20 cm. RZF significantly increased the N apparent recovery efficiency (NARE) and15 N recovery in maize by 14.3–37.8% and 21.9–30.0%, respectively; while decreased N losses by 11.2–24.2%, compared with SSB. The RZF of urea can be considered a slow-release fertilizer, which better matches maize N demand and effectively reduces N losses. Overall, RZF achieved yields as high as the SSB, but with a 20–25% reduction in N application. These results help improve our understanding of N fate in the maize cropping system, and may help guide recommendations for N management in southeastern China.